Remote magnetic navigation versus manual catheter ablation of atrial fibrillation: A single center long‐term comparison. Issue 1 (31st October 2021) - Schlögl, Simon; Schlögl, Klaudia Stella; Haarmann, Helge; Bengel, Philipp; Bergau, Leonard; Rasenack, Eva; Hasenfuss, Gerd; Zabel, Markus
Abstract: Background: Data comparing remote magnetic catheter navigation (RMN) with manual catheter navigation (MCN) ablation of atrial fibrillation (AF) is lacking. The aim of the present prospective observational study was to compare the outcome of RMN versus (vs.) MCN ablation of AF with regards to AF recurrence. Methods: The study comprised 667 consecutive patients with a total of 939 procedures: 287 patients were ablated using RMN, 380 using MCN. Results: There was no significant difference between the groups at baseline. After 2.3 ± 2.3 years of follow‐up, 23% of the patients in the MCN group remained free of AF recurrence compared to 13% in the RMN group ( p  < .001). After analysis of 299 repeat ablations (133 MCN, 166 RMN) there was a significantly higher reconnection rate of pulmonary veins after RMN ablation p  < .001). In multivariable Cox‐regression analysis, RMN ablation was an independent risk factor for AF recurrence besides age, persistent AF, number of isolated pulmonary veins, and left atrial diameter. Procedure time, radiofrequency application time and total number of ablation points were higher in the RMN group. Total fluoroscopy time and total fluoroscopy dose were significantly lower for RMN. Complication rates did not differ between groups ( p  = .842), although the incidence of significant pericardial effusion was higher in the MCN group (seven cases vs. three in RMN group). Conclusions: In our study the AF recurrence rate and pulmonary vein reconnection rate is higher after RMN ablation with a similar complication rate but reduced probability of pericardial effusion when compared to MCN.